Programmed Cell Death in the Leaves of the Arabidopsis Spontaneous Necrotic Spots (sns-D) Mutant Correlates with Increased Expression of the Eukaryotic Translation Initiation Factor eIF4B2 - Gaussand, Gwenael M.; Jia, Qi; Van Der Graaff, Eric; Lamers, Gerda E.; Fransz, Paul F.; Hooykaas, Paul J.; De Pater, Sylvia (Frontiers in Plant Science, 2011)
From a pool of transgenic Arabidopsis (Arabidopsis thaliana) plants harboring an activator T-DNA construct, one mutant was identified that developed spontaneous necrotic spots (sns-D) on the rosette leaves under aseptic conditions. The sns-D mutation is dominant and homozygous plants are embryo lethal. The mutant produced smaller rosettes with a different number of stomata than the wild-type. DNA fragmentation in the nuclei of cells in the necrotic spots and a significant increase of caspase-3 and caspase-6 like activities in sns-D leaf extracts indicated that the sns-D mutation caused programmed cell death (PCD). The integration of the activator T-DNA caused an increase of the expression level of At1g13020, which encodes the eukaryotic translation initiation factor eIF4B2. The expression level of eIF4B2 was positively correlated with the severity of sns-D mutant phenotype. Overexpression of the eIF4B2 cDNA mimicked phenotypic traits of the sns-D mutant indicating that the sns-D mutant phenotype is indeed caused by activation tagging of eIF4B2. Thus, incorrect regulation of translation initiation may result in PCD.